Discovery of benzothiazine derivatives as novel, orally-active anti-epileptic drug candidates with broad anticonvulsant effect. Issue 20 (15th October 2015) - Tanaka, Tomoyuki; Yajima, Nana; Tanitame, Akihiko; Kiyoshi, Tomoko; Miura, Yoshiki
Graphical abstract